1994
DOI: 10.1203/00006450-199401000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cerebral Blood Flow Velocity Fluctuations and Sleep State in Normal Newborns

Abstract: ABSTRAa. Cerebral blood flow velocity was recorded for an average of 23 4-min epochs during natural sleep in 11 normal full-term newborn babies. Intracranial pressure, core temperature, and respiration were simultaneously and non-invasively monitored. Sleep state was classified using information from EEG, pattern of respiration, and eye and body movements by a trained observer. From a total of 238 epochs, 66 were considered to occur in quiet sleep, 101 in active sleep, and in 77 the baby was awake, in a transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
2
22
1
1
Order By: Relevance
“…The similar mean CBFV in quiet and REM sleep has been reported previously [2,8], but the greater amplitude of variability in REM as compared with QS observed in the present study is of interest. REM sleep constitutes the majority of the ultradian sleep cycle of the neonate [17], With increasing maturation, the duration of REM periods shorten, and there is a decline in the amount of REM sleep [18,19], Contrary to our findings in preterm in fants, a significantly greater amplitude of CV in CBFV in QS as compared with REM sleep has been reported in healthy term infants recently [20], As observed in our study, these authors also found that the mean CBFV was similar in the two sleep states. The different findings are most likely related to differences in methodology and in mean gestational age in the two study populations (32 vs 38.5 weeks).…”
Section: Discussioncontrasting
confidence: 56%
“…The similar mean CBFV in quiet and REM sleep has been reported previously [2,8], but the greater amplitude of variability in REM as compared with QS observed in the present study is of interest. REM sleep constitutes the majority of the ultradian sleep cycle of the neonate [17], With increasing maturation, the duration of REM periods shorten, and there is a decline in the amount of REM sleep [18,19], Contrary to our findings in preterm in fants, a significantly greater amplitude of CV in CBFV in QS as compared with REM sleep has been reported in healthy term infants recently [20], As observed in our study, these authors also found that the mean CBFV was similar in the two sleep states. The different findings are most likely related to differences in methodology and in mean gestational age in the two study populations (32 vs 38.5 weeks).…”
Section: Discussioncontrasting
confidence: 56%
“…However no difference in the median cerebral BFV was observed in different sleep states. 28 Several investigations of the renal BFV and RI in children, including a small group of infants during the first year of life, have been performed in cross-sectional studies. 7,[15][16][17] We showed a steady increase of the renal BFV in the same group of healthy infants during the first months of life.…”
Section: -14mentioning
confidence: 99%
“…A wide range of methods have been developed to assess cerebral blood flow control, based on transcranial Doppler measurements of blood flow and recordings of blood pressure [24], but none has proven entirely satisfactory for routine clinical application in neonates. One reason for this difficulty is that cerebral blood flow control involves complex mechanisms, which are affected by many factors [4], [25]- [27]. The current work further demonstrates that spontaneous EEG activity is significantly correlated with CBFV, and this may need to be considered in mathematical models of blood flow control.…”
Section: Discussionmentioning
confidence: 81%
“…Blood flow to the brain changes, for example, with sleep [3], [4], during epileptic seizures [5], [6], and with sensory stimulation [7]. In previous work [8], we investigated the correlation between cerebral blood flow velocity (CBFV), as measured by transcranial Doppler ultrasound, and spontaneous electroencephalogram (EEG) activity during quiet sleep in newborn babies [Tracé Alternant (TA) EEG pattern].…”
mentioning
confidence: 99%